Career Aspirations Among Youth in Manipur: Studying the Barriers to Aspiration in a Conflict Region. (October 2021) - Ningthoujam, Sombala; Bansal, Vishwa Mohan; Singh, Teena; Devi, Oinam Hemlata; Zafar, Maria; Imran, Mohammad
The aim of the study was to explore the career aspirations of the youth in Manipur, and data were collected through focus group discussions from 18 participants. The analysis of the data using thematic analysis was done to identify themes to develop an understanding of what careers these youth aspire for and the barriers to their aspirations. Four major themes identified were aspirations, barriers, support from family, and impact of the insurgency. The participants were found to have high career aspirations, clarity with regard to what they want to achieve in life, and desire to have careers that let them work for the betterment of their community. Limited job opportunities in Manipur and underdevelopment of private sector were attributed as major barriers. Participants from lower socioeconomic status reported facing greater challenge. Emotional as well as monetary support from family facilitated high career aspirations and perseverance in achieving them.